Affordability Homeownership For Socio-Economic Development In Malaysia (Journal of Namibian Studies : History Politics Culture, 2023)
Housing affordability is a good indicator of a nation's socioeconomic development. The goal is to guarantee that the housing offered, which is one of the essential elements, is within the means of all income earner groups, including those who are low-income, middle-income, and high-income. The ultimate goal for most families is to possess a home, which is generally regarded as the criterion of personal achievement. Many people believe that housing prices will continue to rise and become unsustainable during periods of high economic expansion, particularly in the years leading up to the global financial crisis following the COVID-19 recession. This problem arises from both a shortage of supply in the space market and a potential mispricing in the asset market, and may have a spill over effect on surrounding cities due to home purchase restrictions in the developing cities. The housing affordability problem leads to longer commuting time due to the separation of home and workplace, and lower housing space consumption for the residents. This study provide a comprehensive overview of housing affordability in Malaysia based on the a few literature study and general information perspectives. This review study aspires to advance knowledge and comprehension of housing affordability levels for middle-class households and the factors that affect such households' capacity to purchase their first moderately priced homes.